Spatio-temporal variability of urban surface temperature during COVID-19 pandemic: A study from some selected cities in Indonesia and Singapore - Purwantara, Suhadi; Ashari, Arif (Jurnal Wilayah dan Lingkungan, 2024)
Regarding the COVID-19 outbreak, various countries have implemented strict restrictions on community activities to prevent the spread of this outbreak. Restrictions on community activities turn out to have a positive impact on the environment, especially the improvement of Land Surface Temperature (LST) and Surface Air Temperature (SAT). In this paper, the Spatio-temporal variation of LST and SAT in several cities of Indonesia and Singapore during the COVID-19 pandemic is investigated. This study utilizes secondary data from government data and the interpretation of remote sensing imagery. The data were analyzed using remote sensing and statistical analysis using an independent sample t-test to show the comparison. The results of this study indicate that LST in five cities decreased during the period of restriction of community activities. It can be seen from the average value of LST during the pandemic that it was lower than the same period in the previous year. The decline of LST in the zones of industrial activity centers, services, and commuter lines shows the effect of reduced transportation and industry. Meanwhile, the SAT in five cities during the pandemic did not show any difference from the same period in the previous year. The geographical characteristics of these cities in the archipelago are estimated to have contributed to the strong influence of the sea in stabilizing the SAT. In summary, this study provides alternative information on the impact of restrictions on community activities during the pandemic on LST and SAT in Southeast Asia. This study also presents new insights to understand the implications of the pandemic on the environment in the tropical island region cities.